2013
DOI: 10.1016/j.rppneu.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das comorbilidades num programa de reabilitação respiratória em doentes com doença pulmonar obstrutiva crónica

Abstract: PR was associated with improvements in all comorbid subgroups of patients, underlining the important role of exercise training in rehabilitation of those chronic diseases associated with COPD. On the other hand, the presence of comorbidities in COPD patients, if clinically controlled, should not preclude access to PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…The flow chart of the results of the search strategies and the study selection are shown in Figure 1. Comorbidities were either retrieved from the medical record of the patients [16, 17] or were identified based on the Charlson Comorbidity Index [16, 1820]. All articles reported comorbidities to be prevalent among patients with COPD, with a mean percentage of 70% of patients having one or more comorbidities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The flow chart of the results of the search strategies and the study selection are shown in Figure 1. Comorbidities were either retrieved from the medical record of the patients [16, 17] or were identified based on the Charlson Comorbidity Index [16, 1820]. All articles reported comorbidities to be prevalent among patients with COPD, with a mean percentage of 70% of patients having one or more comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary rehabilitation programs were supervised and involved either strength training or both strength and whole body exercise training. In 2 out of 4 articles, pulmonary rehabilitation programs were multidisciplinary [17, 18]. One article reported patients to be referred to standard outpatient rehabilitation, with no detailed description of the program [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with COPD have several comorbidities and are likely to be on other medications 29. Also, physical decon-ditioning due to hyperinflation and cognitive impairment would make the use of multiple inhalers difficult for these patients 10.…”
Section: Discussionmentioning
confidence: 99%